IMPROVING STUDENTS’ WRITING NARRATIVE TEXT BY USING PICTURE SERIES IN POWER POINT PRESENTATION - Susanti, Yuni; Sutapa, Gatot; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis aimed to know the use of picture series in power point presentation in improving students’ writing in narrative text to the tenth grade students of MAN 1 Pontianak. This study was conducted through classroom action research. The subject of this research was 40 students of class X A. The writer worked collaboratively with the English teacher in the class. The writer did three cycles in this research. The data collected through qualitative and quantitative approach. The result of this study showed that the use of picture series in power point presentation can improve the students’ writing in narrative text. Based on the qualitative data, the use of picture series in power point presentation as the media in teaching and learning process helped the students to enjoy and get more attention to follow the lesson. Through picture series the students became more active and involved in teaching learning process. By looking at the order of the picture series in power point presentation the students were able to generate and develop their ideas. Based on quantitative data, the students also gained significant improvement in their writing performance. It could be seen that the students’ writing ability improve from first cycle to the third cycle. It can be concluded that picture series in power point presentation proved the students’ writing ability of tenth A grade students of MAN 1 Pontianak. Keywords: Narrative Text, Picture Series, Power Point Presentation